A Review on Environmental Impact Due to Technological Advancement in Agriculture (International Journal of Innovative Research in Computer Science & Technology, 2022)
griculture is one of India's most vital  sectors, and it is critical for the country's economic survival  and prosperity. Agriculture is the source of livelihood for  around 70% of households and 10% of the urban population.  Today, India is the world's top exporter of agricultural goods  such as the coffee, rice, tea, vegetables, etc. as well as their  preparation and marine products. The Agricultural Researching Systems in the India pinnacle of process that  began the nineteenth century and culminated in the formation  of Indian Councils of Agricultural Research (ICAR) in 1929  recommendation of Royal Commissions on the Agriculture.  The present researching systems, the ICAR primarily assists,  promotes, and collaborates on research and education in India  at the national level. Because farmers strive to feed globe  with the limit naturally resourcing, technologically advancement are the critically to futures of farming. The agri tech solution contributes to the overall expansion of  sustainable agriculture and food production. Agri-tech  startups and disruptive market newcomers are the focus of  the funding. Agriculture output increases as a result of new  technology, resource input, and economic incentives. Future  food-production and handling technological development  should be non-polluting, decrease environmental and health  risks, and not inspire additional governmental restrictions.
Keywords: Agriculture; Economic; Environment; Innovation; Sustainable